Covenant everlasting : Palestine in jewish history - Locker, Berl (New York : Sharon Books, 1947)
Bibliotheek Camille Huysmans
Dedicator: Locker, Berl, dedicatee: Huysmans, Camille
Engels
Monografie
Keywords: Palestijnse kwestie; Palestina